Identifying conservation units after large‐scale land clearing: a spatio‐temporal molecular survey of endangered white‐tailed black cockatoos (Calyptorhynchus spp.). Issue 10 (28th March 2014) - White, Nicole E.; Bunce, Michael; Mawson, Peter R.; Dawson, Rick; Saunders, Denis A.; Allentoft, Morten E.; Austin, Jeremy
Abstract Aim We examined how the threatened and endemic white‐tailed black cockatoos of Western Australia have responded genetically to recent and comprehensive habitat loss with the ultimate aim of identifying units for conservation. We assessed the population structure, connectivity and genetic diversity at spatial and temporal scales for Calyptorhynchus baudinii and C. latirostris, which have undergone dramatic population declines. Genetic comparisons of pre‐ and post‐population decline were carried out by including historical samples dating back to 1920. We examined samples collected from across 700 km of their distribution and sampled approximately 1% of the current population census size to produce significant insights into the population genetics of white‐tailed black cockatoos and generate genetic information crucial for conservation management. Location Southwest corner of Western Australia. Methods Six hundred and eighty‐four cockatoo samples were collected from 1920 to 2010 and profiled with 19 microsatellites to identify spatial population structure and loss of genetic diversity. Results The temporal and spatial microsatellite data illustrated that the geographically defined genetic structuring in white‐tailed black cockatoos is likely to represent a recent phenomenon. We identified: (1) spatial population substructure east and west of extensively cleared habitat (>95, 800 km2), but the historical samples clustered with the current western population, regardless of origin, (2) a regional loss of allelic diversity over 3–4 generations for the current eastern population, (3) a lack of a genetic signal of the recent population decline, but perhaps a mid‐Holocene population collapse and lastly, (4) limited genetic differentiation between the two currently recognized white‐tailed black‐cockatoo species suggests a review of taxonomy and/or management units should be undertaken. Main conclusion Based on extensive spatio‐temporal sampling, we have demonstrated that recent anthropogenic habitat modifications have affected the genetic structure of a long‐lived and highly mobile species. Our results have identified areas of high conservation value and the importance of maintaining native vegetation migration corridors.